2019
DOI: 10.1002/jsfa.9638
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, expression, and functional analysis of polyamine oxidases and their role in selenium‐induced hydrogen peroxide production in Brassica rapa

Abstract: BACKGROUND Selenium (Se)‐induced phytotoxicity has been linked to oxidative injury triggered by the accumulation of reactive oxygen species (ROS) due to the disturbance of anti‐oxidative systems. However, the way Se stress induces hydrogen peroxide (H2O2) production in plants is a long‐standing question. Here we identified the role of polyamine oxidase (PAO) in H2O2 production in the root of Brassica rapa upon Se stress. RESULTS Studying Se‐induced growth inhibition, H2O2 accumulation, and oxidative injury in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Thymolrepressed ammonium transportation may contribute to the decrease in PAOs expression and ROS generation, but we cannot exclude the possibility that thymol may directly regulate the expression of PAOs under ammonium stress. Our previous study has documented that stress-related cis-elements in plant PAO promoters play a role in regulating PAO expression under stress conditions (Wang et al 2019). Thymolmediated physiological adaption involves the modulation of several stress-related signals (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Thymolrepressed ammonium transportation may contribute to the decrease in PAOs expression and ROS generation, but we cannot exclude the possibility that thymol may directly regulate the expression of PAOs under ammonium stress. Our previous study has documented that stress-related cis-elements in plant PAO promoters play a role in regulating PAO expression under stress conditions (Wang et al 2019). Thymolmediated physiological adaption involves the modulation of several stress-related signals (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PAO inhibitor treatment significantly decreased the H 2 O 2 and NO production in tomato under salinity (Takacs et al., 2016), which indicates that PAO may contribute to H 2 O 2 and NO production in order to cope with salinity and that the terminal activities of CuAO and PAO might play a role in cell death induction under lethal salt stress. The PA catabolism is also involved in many other abiotic stress responses, among others, in improved thermotolerance in Nicotiana tabacum by underexpressing the apoplastic PA oxidase (Mellidou et al., 2017), in aluminum-induced oxidative stress of wheat (Yu et al., 2018), in selenium-induced H 2 O 2 production in Brassica rapa (Wang et al., 2019), and in wound-healing by producing the necessary H 2 O 2 for suberin polyphenolic domain and lignin synthesis catalyzed by peroxidase (Angelini et al., 2008).…”
Section: Polyamine Catabolism In Abiotic Stressmentioning
confidence: 99%
“…Recently, besides these three model plants (rice, Arabidopsis, and tomato), some other plant species have also been studied on PAO catabolism, and PAO biological functions. Plant PAOs play important roles in various stress tolerance and the programmed cell death (PCD) events through mediating H 2 O 2 signaling which is generated by stress-induced PAO activity leading to Spd, Spm, and T-Spm oxidation [13,33,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98]. Hatmi et al reported that the grapevine PAO and CuAO activities were upregulated by osmotic stress and Botrytis cinerea infection, suggesting that PA back-conversion and/or terminal catabolism were involved in PA homeostasis under stress conditions [97].…”
Section: Paos In Plantsmentioning
confidence: 99%